2019
DOI: 10.3390/ijerph16071144
|View full text |Cite
|
Sign up to set email alerts
|

Association between Breastmilk LC PUFA, Carotenoids and Psychomotor Development of Exclusively Breastfed Infants

Abstract: The first months of infant life are crucial for proper neurodevelopment, which may be influenced by several factors, including nutrition and nutrients (e.g., long-chain polyunsaturated fatty acids (LC PUFA) and carotenoids) of which the concentration in breastmilk is diet-dependent. This study analysed the relationship between the average concentrations of selected LC PUFA and carotenoids in breastmilk samples from the first and third months of lactation and the psychomotor development of exclusively breastfed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 90 publications
(117 reference statements)
1
55
0
2
Order By: Relevance
“…Substantial evidence also indicates that breastfeeding contributes to better neurodevelopment and psychomotor and cognitive performance and its effect persists over time [9,145,146]. Thus far, it was shown that breastfed children not only obtained better scores on cognitive tests, but also had better brain structural development and physiological activity [147,148,149].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial evidence also indicates that breastfeeding contributes to better neurodevelopment and psychomotor and cognitive performance and its effect persists over time [9,145,146]. Thus far, it was shown that breastfed children not only obtained better scores on cognitive tests, but also had better brain structural development and physiological activity [147,148,149].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Dietary intervention among school-aged children showed that flavanols may act as neuroprotective agents from the effects of air pollution exposure [150]. Moreover, breastmilk contains compounds essential for brain development, intracellular communication, and neurotransmission, i.e., LC PUFAs, brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor (GDNF), choline, gangliosides and sialic acid, lutein and zeaxanthin, and flavonoids [118,121,146,149,152,153,154,155,156,157]. The influence of other maternal factors, such as socioeconomic and psychosocial factors, are not without significance; however, the effect of breastmilk nutrients and bioactive factors is not diminished [146,158].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…A recent study found that the colostrum of mothers that gave birth to premature infants contained lower concentrations of carotenoids as compared to mothers of full-term infants; however, lutein levels were not different, which authors speculate could be related to the significant role of lutein in development of the infant retina and brain [239]. Several studies have analyzed the carotenoid content in human breast milk across diverse populations worldwide [237,[240][241][242][243][244][245][246][247][248][249][250]. These findings demonstrate a strong correlation between dietary intake of carotenoids and the content found in breast milk [178,251,252].…”
Section: Carotenoidsmentioning
confidence: 99%
“…Recent studies have shown the importance of both child-specific inherent characteristics and environmental factors, as well as the interactions between factors related to early childhood cognitive development [ 5 ]. However, research generally emphasizes the child or the environment, and the peripheral factors that influence cognitive ability are seldom taken into account [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. The complex inter-relationships between chemical and non-chemical stressors and their possible collective/synergistic/antagonistic effect(s) on cognitive development have yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…To date, this review is the most comprehensive analysis of the interactions of chemical and non-chemical stressors from the total environment on childhood cognitive development. Eleven studies published since 2016 have used Ruiz et al [ 48 ] as a springboard to examine the effects of specific stressors such as neighborhood chaos, industrial pollution, environmental contaminants, socioeconomic status, and poverty on childhood cognitive development [ 6 , 7 , 28 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Recent publications related to childhood cognitive development that do not cite Ruiz et al [ 48 ] focus on the effects of postnatal care, maternal mental health, and physical brain characteristics [ 57 , 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%